2023
DOI: 10.1021/acsmaterialslett.3c00115
|View full text |Cite
|
Sign up to set email alerts
|

Volatile 2-Thiophenemethylammonium and Its Strongly Bonded Condensation Product for Stabilizing α-FAPbI3 in Sequential-Deposited Solar Cells

Abstract: The perovskite films prepared by the sequential deposition method suffer from incomplete lead iodide (PbI2) reaction, which is manifested by the poor photostability of the prepared perovskite solar cells. Herein, 2-thiophenemethylammonium (TMA), known for the formation of Ruddlesden–Popper layered perovskites, is used to modify the PbI2 film. The introduction of TMA reduces the crystallinity of PbI2 and participates in the formation of the solvent intermediate phase, thus promoting the formation of α-formamidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Other reports have suggested that the A′ cation of 2D perovskites incorporated into FAPbI 3 volatilized completely during annealing except for a small fraction left at grain boundaries ( 19 , 38 , 39 ), which would also explain the disappearance of our 2D signal over time and the slow increase in the (001) 3D peak intensity during annealing at 150°C. Solid-state 1 H NMR on scraped films of FAPbI 3 with added 2D before and after annealing did reveal a partial volatilization of the spacer cation during film formation but also confirmed appreciable fractions of BA and PA even after annealing at 150°C for 20 min (figs.…”
Section: Crystallization Dynamics Of 2d-templated Fapbi3 Thin Filmsmentioning
confidence: 63%
“…Other reports have suggested that the A′ cation of 2D perovskites incorporated into FAPbI 3 volatilized completely during annealing except for a small fraction left at grain boundaries ( 19 , 38 , 39 ), which would also explain the disappearance of our 2D signal over time and the slow increase in the (001) 3D peak intensity during annealing at 150°C. Solid-state 1 H NMR on scraped films of FAPbI 3 with added 2D before and after annealing did reveal a partial volatilization of the spacer cation during film formation but also confirmed appreciable fractions of BA and PA even after annealing at 150°C for 20 min (figs.…”
Section: Crystallization Dynamics Of 2d-templated Fapbi3 Thin Filmsmentioning
confidence: 63%
“…These interesting in situ chemical reactions occurring between the neutral amines or other molecules, such as bis-diazirine, and the organic cation(s) of the precursor material offer huge potential for further exploration/improvement in PSCs and other perovskite-based applications. In particular, precisely targeted chemical reactions or surface species can be implemented into the perovskite system for specific aims. , Various unexpected/underexplored chemical reactions generated in this complex system also make the perovskite research more exciting.…”
Section: Interface Engineering For Solar Cellsmentioning
confidence: 99%
“…Methylenediammonium (MDA 2+ ) also oligomerizes into hexamethylenetetramine (HMTA), which can then react with FA + to form tetrahydrotriazinium (THTZ-H + ) . These reactions can potentially happen at the solid film surface, for example, when it is modified with 3-(aminomethyl)­pyridine (3-APy) and likely 2-thiophenemethylamine (TMA), EDA, and other alkylamines. , In the case of 3-APy, the product is N -(3-methylpyridine) formamidinium (MPyFA + ), or for amine-MA + reaction, a simple transfer or sharing of acidic protons happens, forming 3-APy + . The authors further claimed that the formed MPyFA + cation sits at the A-site of the perovskite, with the pyridine ring promoting the formation of positively charged V I (iodide vacancies), which act as shallow donors and induce a field that facilitates electron extraction.…”
Section: Interface Engineering For Solar Cellsmentioning
confidence: 99%